2010
DOI: 10.1007/s11661-010-0302-7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Σ9 Boundaries in Grain Boundary Engineering

Abstract: In a grain-boundary-engineered (GBE) microstructure, R9 boundaries are the second most abundant boundary type. This article presents data showing that, in GBE copper, most R9s were special. R9 boundaries are also a geometrically necessary component of a GBE microstructure. It is suggested that there are competing requirements for R9s; during iterative GBE processing, they are required to be mobile, whereas afterward, it is desirable that they are special boundaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…More importantly, fractions of Σ9 + Σ27 increased from 3.4% (AR) to 10.2% (ARGBE). An increase in the Σ9, Σ27 fractions has been attributed to the Σ3 regeneration model proposed by Randle et al [32,33]. In addition, triple junction fractions extracted from the orientation maps show a sharp drop in fraction of J0 type from 48% to 10%.…”
Section: Microstructurementioning
confidence: 77%
“…More importantly, fractions of Σ9 + Σ27 increased from 3.4% (AR) to 10.2% (ARGBE). An increase in the Σ9, Σ27 fractions has been attributed to the Σ3 regeneration model proposed by Randle et al [32,33]. In addition, triple junction fractions extracted from the orientation maps show a sharp drop in fraction of J0 type from 48% to 10%.…”
Section: Microstructurementioning
confidence: 77%
“…In this context, GBs − specifically the energy of GBs − has been explored as a way to make a material more thermally stable and resistant to crack nucleation: As random high‐angle GBs (HAGBs) and their conjunctions are often prone to crack nucleation, one approach is to enhance the fraction of coincidence site lattice (CSL)‐GBs, with low normalΣ, which relates to their relatively low excess energy . Of special interest are normalΣ3‐GBs, with a specific interest in the triple junction (TJ) that these GBs are part of . For instance, Kobayashi et al observed no intergranular fatigue cracks at TJs consisting only of normalΣ‐GBs …”
Section: The Selected Annealing Temperatures (Isochronal Annealing) Umentioning
confidence: 99%
“…CSL boundaries are characterized by misorientations that allow atoms from neighboring lattices to 2 Journal of Materials coincide notionally [11]. The fraction of atoms that coincide at the boundary is called the density of coincidence sites [11].…”
Section: Introductionmentioning
confidence: 99%
“…CSL boundaries are characterized by misorientations that allow atoms from neighboring lattices to 2 Journal of Materials coincide notionally [11]. The fraction of atoms that coincide at the boundary is called the density of coincidence sites [11]. The reciprocal of this density of the coinciding sites is used to describe a CSL boundary and is designated as Σ [12,13].…”
Section: Introductionmentioning
confidence: 99%